2004
DOI: 10.1063/1.1807282
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical approaches, contextual variables, and the development of student self-efficacy in undergraduate physics courses

Abstract: Self-efficacy, or a person's situation-specific belief that s/he can succeed in a given task, has been successful in a variety of educational studies for predicting behaviors such as perseverance and success (grades), and for understanding which behaviors are attempted or avoided. The focus of this study was to examine if classroom factors such as teaching strategies and classroom climate contribute to students' physics self-efficacy. 121 undergraduates in first semester, calculus-based introductory physics co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 7 publications
1
26
0
2
Order By: Relevance
“…Britner and colleagues have looked at levels of self-efficacy for middle school [39] and high school students [40] and what differences might exist between science domains. Other self-efficacy research focuses on college courses, including domains such as physics [37,41,42], or focuses on the selfefficacy for teaching science rather than learning science [43][44][45][46]. Investigating self-efficacy in different domains will help researchers understand the nature of this complex variable, and can lead instructors toward understanding how self-efficacy in their own content areas might be improved.…”
Section: Domain-specificity: Self-efficacy In Astronomymentioning
confidence: 99%
See 1 more Smart Citation
“…Britner and colleagues have looked at levels of self-efficacy for middle school [39] and high school students [40] and what differences might exist between science domains. Other self-efficacy research focuses on college courses, including domains such as physics [37,41,42], or focuses on the selfefficacy for teaching science rather than learning science [43][44][45][46]. Investigating self-efficacy in different domains will help researchers understand the nature of this complex variable, and can lead instructors toward understanding how self-efficacy in their own content areas might be improved.…”
Section: Domain-specificity: Self-efficacy In Astronomymentioning
confidence: 99%
“…We hypothesized that postinstruction self-efficacy (compared to interest) would be more strongly related to change in understanding of star properties over the course of instruction. Based upon prior research in physics and astronomy education [41] and the study's context, we further hypothesized that all three variables (understanding, self-efficacy, and interest) would increase significantly over a semester-long course. We also predicted that an increased attention to mastery and vicarious experiences within the instructional designs and implementation could lead to improvements in these variables over the courses.…”
Section: The Present Studymentioning
confidence: 99%
“…We present this as a limitation of our study and for that reason we report on analyses of each source of self-efficacy separately, in addition to students' total score on the SOSESC-P, which we interpret as a proxy for student self-efficacy. We do so on the grounds that we found significant change on all four sources of self-efficacy and criteria established by past studies [39,44,46,47,59].…”
Section: A Self-efficacy Survey: Strengths and Limitationsmentioning
confidence: 82%
“…The investigation of relating literature shows us that many studies have been carried out in various countries on physics [3], chemistry [4], science [5,6], math's [7], science teaching [8] and biology [9]; in addition to tax research [10] and infant care [11]. As we can see, self-efficacy is adopted to many fields and disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Research in educational and vocational psychology has found that self-efficacy is very effective for explaining perseverance and success across the educational spectrum, including undergraduate education and science related majors [6].…”
Section: Introductionmentioning
confidence: 99%